PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA SISWA - Ulyah Puspita Ayu; Suci Pratiwi Tahir; Andi Paida (Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to improve the mathematics learning outcomes of class II students at UPTD SDN 19 Barru through the application of the Problem Based Learning (PBL) learning model. This research uses the Classroom Action Research (CAR) method with two cycles. The research subjects were 11 students registered for class attendance in the 2023/2024 school year. The research procedure consists of four stages, namely planning, action, observation and reflection which are carried out repeatedly in each cycle. Each cycle consists of four meetings, with three face-to-face meetings and one meeting for a learning outcomes test. Data collection techniques use observation, documentation, and learning outcomes tests. Data was analyzed descriptively qualitatively to determine the development of student learning outcomes. The research results show that the PBL model can increase students' motivation and mathematics learning outcomes. In cycle I, the average student score was 54.5%, while in cycle II it increased to 81.8%. Based on these results, it can be concluded that the application of the PBL model is effective in improving the mathematics learning outcomes of class II students.